The relationship between human resource management and organizational culture in public hospitals - Buchelt, Beata Irma; Jończyk, Joanna Anna (Journal of Public Governance, 2017)
Organizational culture (OC), along with organizational structure or strategy, is one of the most crucial determinants of successful human resource management practices implementation. The factor’s importance increases in unique organizations such as public hospitals. In the literature, the aspect of organizational culture in hospitals is widely discussed. However, at the same time researchers rarely focus on the inf luence of OC on human resource management practices. Due to the fact, the paper’s objective is to detect relationships between organizational culture and human resource management practices. In order to fulfil the objective, in the first part of the paper the authors discuss theoretical aspects of OC and HRM in public hospitals. In the second part, they analyze the relationship between these two categories. Additionally, a research was conducted in the years 2014/2015 in Poland on the sample of 468 respondents employed in 8 public hospitals. Its results confirm that there is a correlation between different types of organizational culture and particular human resource management practices such as recruitment of employees who are open to change and development and ready to share knowledge and reward staff for innovativeness. The findings can be regarded as reasonable premises for management in the organizations and a further research area.